Gallstone ileus: an unfortunate complication after endoscopic biliary drainage - Dinesh Baithma Jothi; Dexter Lai Zen Ran; Sanjeev Sandrasecra; Firdaus Hayati (Scientific Foundation SPIROSKI, 2020)
Gallstone ileus is a misnomer of intestinal obstruction. This rare entity of gallstone disease happens after episodes of acute cholecystitis, Mirizzi’s syndrome, or even after endoscopic intervention. A 17-year-old lady with acute cholecystitis, hepatolithiasis, and choledocholithiasis was endoscopically managed through endoscopic retrograde cholangiopancreatography. She was initially well but complicated with intestinal obstruction the next day. The abdominal radiograph and computed tomography showed a dilated small bowel secondary to gallstone ileus. An emergency laparotomy was performed to relieve the obstruction. Gallstone ileus is a rare cause of intestinal obstruction. It must be suspected in a patient with underlying gallstone disease, especially after an endoscopic biliary intervention. Emergency enterotomy and stone extraction are the imperative surgical intervention if the stone is not able to pass out spontaneously.